2008
DOI: 10.1007/s11947-008-0143-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of High-Hydrostatic-Pressure Effects on Fresh Produce Using Chlorophyll Fluorescence Image Analysis

Abstract: High hydrostatic pressure has the potential to affect food-related enzymes and microorganisms while retaining the produce's characteristic properties. Although many studies on effects of high pressure on quality attributes of fruit and vegetables have been published, experimental results on the impact of high-pressure treatment on the physiological activity of products are rare. To characterize changes of the samples fast and noninvasive methods as well as a sensitive biological model system are required for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 40 publications
(52 reference statements)
1
33
0
Order By: Relevance
“…In subsequent years, various alternative substances, such as honey, citric acid, ascorbic acid, calcium chloride, calcium lactate, calcium ascorbate and even fruit juices have been used to retard browning in fresh-cut fruit (Jeon & Zhao, 2005;Lozano-de-Gonzalez, Barrett, Wrolstad, & Durst, 1993;Oms-Oliu et al, 2010)-albeit with often limited success as it was difficult to achieve efficient browning inhibition. Numerous studies dealt with innovative physical treatments (Ramos, Miller, Brandão, Teixeira, & Silva, 2013) such as high isostatic pressure (Schlüter, Foerster, Geyer, Knorr, & Herppich, 2009) being recently suggested for the application on some foods in order to inactivate enzymes without the degradation in flavor and nutrients associated with traditional thermal processing (Oliva & Barbosa-Canovas, 2005). Much attention has particularly been paid to pulsed electric fields (Barbosa-Cánovas, Góngora-Nieto, & Swanson, 1998;Knorr & Angersbach, 1998;Mertens & Knorr, 1992) and UV-or gammairradiation and packaging in modified atmosphere (Hassenberg, Huyskens-Keil, & Herppich, 2012;Lescano, Narvaiz, & Kairiyama, 1993;Poubol, Lichanporn, Puthmee, & Kanlayanarat, 2010;Sothornvit & Kiatchanapaibul, 2009) during recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent years, various alternative substances, such as honey, citric acid, ascorbic acid, calcium chloride, calcium lactate, calcium ascorbate and even fruit juices have been used to retard browning in fresh-cut fruit (Jeon & Zhao, 2005;Lozano-de-Gonzalez, Barrett, Wrolstad, & Durst, 1993;Oms-Oliu et al, 2010)-albeit with often limited success as it was difficult to achieve efficient browning inhibition. Numerous studies dealt with innovative physical treatments (Ramos, Miller, Brandão, Teixeira, & Silva, 2013) such as high isostatic pressure (Schlüter, Foerster, Geyer, Knorr, & Herppich, 2009) being recently suggested for the application on some foods in order to inactivate enzymes without the degradation in flavor and nutrients associated with traditional thermal processing (Oliva & Barbosa-Canovas, 2005). Much attention has particularly been paid to pulsed electric fields (Barbosa-Cánovas, Góngora-Nieto, & Swanson, 1998;Knorr & Angersbach, 1998;Mertens & Knorr, 1992) and UV-or gammairradiation and packaging in modified atmosphere (Hassenberg, Huyskens-Keil, & Herppich, 2012;Lescano, Narvaiz, & Kairiyama, 1993;Poubol, Lichanporn, Puthmee, & Kanlayanarat, 2010;Sothornvit & Kiatchanapaibul, 2009) during recent years.…”
Section: Introductionmentioning
confidence: 99%
“…High hydrostatic pressure (HHP) has already become a commercially implemented technology, spreading from its origins in Japan, followed by USA and now Europe, with worldwide take-up increasing almost exponentially since 2000 (Sun and Norton 2008;Heinz and Bukow 2010). HHP processing offers advantages over conventional processing techniques, but there are factors that may limit its applicability to some fish products (Ohshima et al 1993;Schlüter et al 2009). Potential detrimental changes, in appearance, texture and chemical parameter, in HHP-treated products are also dependent on the processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that rheological properties of fruit concentrate depend greatly on the method of concentration of juice/pulp (Dak et al 2008;Sabanis et al 2008;Schlüter et al 2009). In this respect, it has been reported that the apparent viscosity of tomato purées prepared from hot break extracted juice by evaporation was much higher than that made by centrifuging out the insoluble solids, concentrating the serum, and then reconstituting (Harper and El Sahrigi 1965).…”
Section: Introductionmentioning
confidence: 99%